Pertanggungjawaban Pidana atas Keracunan Makanan dalam Program Makan Bergizi Gratis (MBG): Analisis Asas Kausalitas dan Pertanggungjawaban Korporasi - Anesa Megawati Purada Siringoringo; Aristoteles Aristoteles; Claudia Yuni Pramita; Kristian Kristian (Universitas Medan Area, 2026)
The Free Nutritious Meal Program (MBG) is a government policy aimed at improving public nutrition and reducing stunting rates. However, its implementation has the potential to pose a risk of food poisoning, which can impact public health. This study aims to analyze the provisions of criminal liability for food poisoning in the implementation of the MBG Program and determine legal subjects who can be held criminally accountable. This study uses a normative legal research method with a legislative approach and a conceptual approach. This research is motivated by the normative gap in Presidential Regulation Number 83 of 2024 and Presidential Regulation Number 115 of 2025, which do not yet regulate in detail the mechanism of criminal liability in the event of food poisoning in the MBG Program. The results of the study indicate that criminal liability can be based on the provisions of the Criminal Code, the Food Law, and the Health Law through the application of the principle of causality to determine the relationship between actions and their consequences. In addition to individuals, corporations as food providers can be held criminally accountable through a strict liability approach if harm to public health arises from food products that do not meet safety standards. The application of criminal penalties is carried out while still observing the principle of ultimum remedium. This research contributes to the development of food criminal law and strengthening legal protection for the community in the implementation of the MBG Program, and recommends strengthening criminal liability regulations in the implementation of the program.